2011
DOI: 10.1016/j.jcv.2010.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex reverse transcription PCR Luminex assay for detection and quantitation of viral agents of gastroenteritis

Abstract: Background-Several viruses can cause diarrheal disease, a leading cause of morbidity and mortality worldwide. Existing diagnostic methods include ELISA and nucleic acid amplification, usually performed individually.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
75
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 29 publications
1
75
0
Order By: Relevance
“…It was clear from the distribution of different pathogens identified in the study ( Table 1) that the etiology of diarrhea is complex and in a substantial proportion of samples, pathogens were not identified. Development of an enteric pathogen testing panel and discovery of novel pathogens using cutting edge technologies such as MassTag PCR, Taqman array or Luminex assays would be required to explore the true burden of pathogens in greater detail [14,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…It was clear from the distribution of different pathogens identified in the study ( Table 1) that the etiology of diarrhea is complex and in a substantial proportion of samples, pathogens were not identified. Development of an enteric pathogen testing panel and discovery of novel pathogens using cutting edge technologies such as MassTag PCR, Taqman array or Luminex assays would be required to explore the true burden of pathogens in greater detail [14,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, SaVs were common during the winter months and in younger children [1]. Sapovirus prevalence has only been described in a few sub-Saharan African countries, including Kenya (5.7% in <14 years) [6], Tanzania (5.7-6.4% in <5 years) [7,8], Malawi (8% in <5 years) [9], South Africa (SA; 4.1-8.4% in all ages) [10,11], Gabon (9.5% in <5 years) [12] and Burkina Faso (18% in <5 years) [13]. These studies utilized molecular methods for SaV detection with an average prevalence of 7.5% (95% CI 3.4%-11.5%) among diarrhoeal cases.…”
Section: Introductionmentioning
confidence: 93%
“…In Tunisia, SaVs were reported in paediatric outpatients with gastroenteritis and only GI.1 was identified [15]. Sapoviruses have also been reported in patients hospitalised with gastroenteritis in Tanzania [16] and in Malawi [17]. Genotypic characterisation was not conducted in the Tanzanian study [16] and in Malawi, only GII strains were identified [17].…”
Section: Introductionmentioning
confidence: 99%
“…Sapoviruses have also been reported in patients hospitalised with gastroenteritis in Tanzania [16] and in Malawi [17]. Genotypic characterisation was not conducted in the Tanzanian study [16] and in Malawi, only GII strains were identified [17]. Five different SaV genotypes were identified in HIV-seropositive children in Kenya [18].…”
Section: Introductionmentioning
confidence: 99%